A Retrospective Analysis on Poison Related Mortalities in a Tertiary Care Centre in Pakistan - Zohaib Abubaker; Maheen Nisar; Ahmed Jamshed; Mohammad Abbas; Kayhan Hashmi; Muhammad Arsalan (Asia Pacific Journal of Medical Toxicology, 2020)
Background In Pakistan, most of the data on poisoning comes from scattered case series with data on poisoning mortality, and especially relating to people of lower socioeconomic status, lacking. We aim to shed some insight on the factors relating to poisoning mortality in Pakistan in an effort to appreciate the potential measures required to reduce it Methods A total of 204 cases of poisoning fatalities, occurring between May 29, 2013, and September 10, 2019, were reviewed retrospectively from the National Poison Control Centre at Karachi, Pakistan. Cases of poisoning by accident, suicide, and homicide were included and animal bites and food poisoning were excluded. Patients less than 13 years of age were excluded. Results From our deceased patient medical records, 67.2% were males and 32.8% were females. The mean age of the patients was 29.20 ± 13.04 years. Most of the deaths from poisoning were attributed to organophosphate consumption, mainly through the ingestion of rat killer (30.9%), dichlorvos based pesticide (23.5%), and insecticides (10.3%). A noteworthy number of the deceased patients were housewives (12.7%) and students (11%) and a significant association was seen between occupation and poison consumed (p=0.048). Treatment for most of the cases was non-specific.   Conclusion Poisoning is a serious threat to all demographics and mortality can be attributed to substances that can be easily obtained and are widely used. This indicates a gap in safety measures and calls for tighter regulation standards.